EFFECT OF E-MARKETING AND E-COMMERCE TOWARD SMALL ENTERPRISES’ REVENUE IN FOOD SECTOR DURING COVID-19 PANDEMIC - Angela, Cindy (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2022)
This study aims to determine the effect of E-Marketing and E-Commerce on the revenue of micro-enterprises in the food sector during the Covid-19 pandemic. This study uses quantitative data methods and the source data is primary data. The population in this study were micro-enterprises in the food sector in Belawan City, Medan-Belawan District, amounting to 54 businesses. The sample in this study used purposive sampling with the criteria of business actors selling rice with a total of 30 samples. Data analysis and testing consisted of validity test, reliability test, descriptive statistics, classical assumption test, multiple regression analysis, partial hypothesis testing (t test) and simultaneously (F test), and coefficient of determination test. The data were analyzed by providing equations using the multiple linear regression analysis method. The results of the analysis give the equation Revenue = 10,411 – 088 E-Marketing + 558 E-Commerce + e . The results of this study indicate that E-Marketing has no effect and is not significant on the Revenue of Micro Sub Food Business based on a partial hypothesis test, namely the value of tcount > ttable with a value of -0.806 > 2.04841 and a significant value < 0.05, with a value of 0.427 > 0.05. The results of the analysis show that E-Commerce has a significant effect on Sub-Food Micro Business Revenue based on a partial hypothesis test, namely the value of tcount > ttable with a value of 8.936 > 2.0243 and a significant value of < 0.05, with a value of 0.000 < 0.05. The results showed that E-Marketing and E-Commerce had a significant effect on Sub-Food Micro Business Revenue based on the simultaneous hypothesis results, namely Fcount > Ftable with a value of 40.111 > 3.35 and a significant value of < 0.05, with a value of 0.000 < 0.05. The results of this study are supported by the value of R Square (R2) = 0.748 or 74.8%, which means that E-Marketing and E-Commerce simultaneously have an effect of 74.8% on the Revenue of Micro Sub-Food Business, while the remaining 25.2% of the Revenue tariff variable can be affected by other variables not examined in this study such as business location, capital, and price perception.